RELATIONSHIPS BETWEEN CORE ENDURANCE, HIP STRENGTH, AND BALANCE IN COLLEGIATE FEMALE ATHLETES - Ambegaonkar, Jatin P. (Sports Physical Therapy Section, 2014)
PURPOSE/BACKGROUND: Lower extremity injuries such as Anterior Cruciate Ligament (ACL) tears remain a concern in collegiate female athletes. Core endurance and hip strength reportedly influence ACL and lower extremity injury risk. Good neuromuscular control, as measured by the Star Excursion Balance Test (SEBT) test is associated with decreased lower extremity injuries. The exact relationships between core endurance, hip strength, and balance (SEBT scores), and how they impact one another in the female collegiate athlete remain unclear. Thus, the purpose of this study was to investigate relationships between core endurance, hip strength, and balance in collegiate female athletes. METHODS: Forty collegiate female athletes (19.6±1.1yrs, 163.1±7.8cm, 61.3±6.5kgs) performed the SEBT in anterior, posterolateral, and posteromedial directions bilaterally (% leg length), McGill's anterior, posterior, and left and right plank core endurance tests (seconds), and hip abductor, flexor, extensor, and external rotator isometric strength tests bilaterally (N) using handheld dynamometry. Pearson's product moment correlations examined relationships between core endurance, hip strength, and balance. A linear regression analysis examined whether core endurance and hip strength influenced balance (p≤0.05). RESULTS: Anterior SEBT scores were fairly positively correlated with hip flexor and extensor strength. Posterolateral SEBT scores were fairly positively correlated with hip abductor, extensor, and flexor strength (p=0.02‐to‐0.004; r=0.26‐to‐0.45). Fair positive correlations existed between posterior core endurance and hip extensor strength bilaterally (right: p=0.02, r=0.37; left: p=0.003, r=0.47). Core endurance and SEBT scores were not correlated (p>0.05). Core endurance and hip strength did not influence SEBT scores (p=0.47). CONCLUSIONS: Overall, hip strength, but not core endurance was related to SEBT scores in collegiate female athletes. Females with greater hip flexor, extensor, and abductor strength also had better anterior and posterolateral SEBT scores. Having females participate in hip muscle strengthening programs may help improve their SEBT balance scores, as a measure of their neuromuscular control and influence their ACL and lower extremity injury risk. LEVEL OF EVIDENCE: 2b